Teaching English using a genre pedagogy to Islamic junior high school students - Aunurrahman Aunurrahman; Any Hikmayanti; Yuliana Yuliana (Journal on English as a Foreign Language, 2020)
This descriptive qualitative study aims to find out how a genre pedagogy is used to teaching the English language. A class consisted of thirty-six students of a public Islamic junior high school was selected purposefully as participants. The data collection involved participant observation, field notes, and documents, in this case, the students' works. The participant observations were conducted in four meetings. During the observations, this study collected the students’ works purposefully. The data analysis used two techniques, namely the thematic analysis to analyze the field notes and functional grammar framework to analyze the students’ independent construction texts. The findings of the study reveal that the students could practice daily life texts in pairs and write a daily life text independently, critically, and creatively as they managed to work on their own and to use specific information, expressions, and contexts in their texts as demanded by the government and the 21st century. This could be achieved as the researcher applied genre pedagogy teaching procedures, explicit teaching, and scaffolding to ensure the students could do the work effectively. This study suggests teachers apply genre-pedagogy teaching procedures and principles to ensure the students could learn English better.